Scaffolding academic literacy in a diverse first-year higher education classroom: evaluating the effectiveness of a blended learning model - Schneider, Britta; Zammit, Brian; Armstrong-Roper, Mark (Journal of Academic Language and Learning, 2017)
The differing levels of academic preparedness of commencing students and the provision of institutional support with respect to academic and information literacy present universities with a number of challenges. This paper discusses the effectiveness of an innovative and integrated blended learning model to scaffold and embed the teaching and learning of university literacy practices in a first-year Arts unit. The Action Research project ran over the course of two semesters and found increasing collaboration between discipline, Academic Language and Learning as well as Library staff to be key to the success of this multi-layered strategy. Analysis of educators’ in-class experiences, student feedback and site traffic data suggests that a collaborative blended learning model effectively enhances the first-year experience for all stakeholders.